2020
DOI: 10.1155/2020/8383010
|View full text |Cite
|
Sign up to set email alerts
|

Short Shoot Growth and Reproduction Response to Light Conditions Vary with Order Branching in the Proximal Part of C. atlantica Crown

Abstract: is study compared the effects of shading in individual branch orders 2 and 3 on the needle survival, growth, and reproduction of five categories of short shoots of the proximal part of wild Atlas cedar (Cedrus atlantica (Endl.) G. Manetti ex Carrière). e sun exposure did not affect the number of short shoots in the two branch orders, whereas light compared to shade only stimulates the unbranched short shoot elongation of the branch order 3. e impact of shade exposure compared to sun on the loss of needles depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(84 reference statements)
0
1
1
Order By: Relevance
“…is difference may be due to the use of the needles from the long shoots, which are generally longer than those of whorls. On the other hand, values obtained in the present study are still low even when compared to those of C. atlantica whorl needles reported by Saouab and Bendriss Amraoui [53] or to those of the needles of young seedlings of 2-5 years in the Middle Atlas of Morocco and higher than those of 16 months and 2 years of Algerian provenances [54]. e values of the average length of needles of the populations of Aït Ayach and Aït Oufella that were found to be included in the margin of length 10.77-11.06 mm are lower than those found in this study Tamrabta and Moudemame ones (Table 2).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…is difference may be due to the use of the needles from the long shoots, which are generally longer than those of whorls. On the other hand, values obtained in the present study are still low even when compared to those of C. atlantica whorl needles reported by Saouab and Bendriss Amraoui [53] or to those of the needles of young seedlings of 2-5 years in the Middle Atlas of Morocco and higher than those of 16 months and 2 years of Algerian provenances [54]. e values of the average length of needles of the populations of Aït Ayach and Aït Oufella that were found to be included in the margin of length 10.77-11.06 mm are lower than those found in this study Tamrabta and Moudemame ones (Table 2).…”
Section: Discussioncontrasting
confidence: 91%
“…On seedlings of provenances from the High Atlas (Tounfite and Assaka) grown in Maures, Arbez et al [54] found values of the average length of needles of 23.8 and 19.5 mm, respectively. ese comparisons show that the average length of cedar needles is highly dependent on shoot growth and environmental conditions [53], making it one of the most important varietal selection criteria for cedar if it was taken at a fully developed stage. us, the ontogenetic variations of the needle traits may not mislead when we use mature needles to distinguish the ecotype in this study.…”
Section: Discussionmentioning
confidence: 99%